Menggambarkan Manfaat Program Parenting Menurut Orang Tua di Kecamatan Lubuk Sikaping Kabupaten Pasaman - Rahmatika Azhari; Irmawita Irmawita; Wirdatul Aini (Universitas Negeri Padang, 2018)
This research is motivated by the high participation of parents in following parenting activity. This is due to the smooth program parenting program by parents. This study aims to illustrate the benefits of parenting programs by mothers who participate in parenting programs that include: childcare, childcare, parenting, and child care. This research includes quantitative descriptive research that describes the data as it is. The population numbered one hundred seventy one people and the sample amounted to fifty two people determined based on sampling technique that is random sampling technique. The data collection tool uses questionnaires and data analysis using the percentage formula. The results found that; 1) a description of the benefits of the parenting program seen from the parenting time of the parent looking good, 2) description of the benefits of the parenting program seen from the parenting material according to the parent looking good, 3) the benefits of the parenting program seen from the parenting parents who look good, 4) a picture of the benefits of parenting programs see from parenting by the parents look good. Suggestions for the motivation of parents to want to enter their children into early childhood and participate in activities held by early childhood.